Ferramenta para auxílio no ajuste de carga de herbívoros em sistemas pastoris - (:unkn) unknown (Universidade Federal do Pampa, 2020)
The present work aims to build a spreadsheet to be used as a tool to adjust animal stock rate in farms. For this purpose, a search for bibliographic information was carried out, obtained through scientific articles. The information used was the accumulation rates (dry matter yield/ha/day) of different forages and the nutritional need of the different animal categories that can compose the herd. The spreadsheet presents the calculation of the estimated quantity of animals to be used per hectare, under the chosen conditions. The user of the spreadsheet chooses the month, the available pasture, a supplement, if necessary and forage management. As soon as every month is informed, a graph will be generated that shows throughout the year in which month there was a positive or negative balance in the forage supply for the herd. The results obtained by the spreadsheet showed similarity with data from farms in the region of the western border of RS and with data from the literature. The use of the spreadsheet as a tool can assist the user in decision-making.
Tool to feed budget of herbivores in pastoral systems
Keywords: Plantas forrageiras; Pastoreio contínuo; Tecnologia no campo; Forage plants; Continuous grazing; Technology in the field; CNPQ::CIENCIAS AGRARIAS